Moscow and Greek communism, 1944-1949 - Stavrakis, Peter J., 1955- (Cornell University Press, 1989)
Moscow and Greek Communism is the first comprehensive analysis of Soviet conduct in Greece during the most critical period of Greek history in this century-the last months of World War II and the years of the Greek Civil War. Peter J. Stavrakis demonstrates that Soviet policy in Greece was highly mutable and reveals how its shifts were governed by Moscow's changing aims in the Near East generally, Soviet policy toward the Western powers, and the constantly changing Greek political situation. Stavrakis draws on previously inaccessible evidence from Greek Communist archives, recently declassified materials from the U.S. National Archives, documents from British archives, and personal memoirs of former Greek partisans to create the most accurate picture available of developments in the Balkans between 1944 and 1949. He traces the course of Soviet policy, explaining why Stalin vacillated in his attitude toward the armed insurgency of the Greek Communist party (KKE), finally acting in a way that ensured its defeat. Students of Soviet foreign policy will want to consider his thesis that the lessons learned in Greece have continued to guide Soviet interventionism in regions where its capabilities for control are limited.